When Men Report More: Paradoxical Gender Perceptions of Discrimination in the Lebanese Hospital Sector - Saleh, Lena; Al Hassanieh, Dima; Badran, Jana (International Review of Management and Marketing, 2026)
Gender discrimination remains a persistent barrier to equitable participation in the workforce, particularly within healthcare systems where women are numerically dominant yet structurally disadvantaged. This study investigates perceptions of workplace gender discrimination among male and female employees in the Lebanese hospital sector. Drawing on survey data from more than 300 respondents across hospitals in North Lebanon, the research employs quantitative methods to compare gendered perceptions and assess how organizational factors—including human resource management practices, rewards, workplace support, and stressors—shape these views. Results reveal a paradoxical finding: male employees reported higher levels of perceived discrimination than their female counterparts. The present findings contribute to a growing body of evidence suggesting that the assumption of inevitable and uniform discrimination against women in Middle Eastern healthcare contexts is overstated. Rather than a monolithic reality, gendered experiences of work appear to be contingent upon occupational role, institutional arrangements, and broader socio-cultural conditions. In this sense, discrimination is better understood as context-dependent, manifesting differently across professional groups and organizational levels, and shaped by both cultural norms and the positionality of the individual reporting the experience. The study contributes to the literature by providing micro-level evidence from Lebanon, a context characterized by political struggles, recurrent wars, and comparatively weak infrastructure (Saleh l.& Kinaan. A , 2001). Practical implications are offered for hospital administrators, HR practitioners, and policymakers seeking to design inclusive workplace policies and leadership pathways.